STRATUP BISNIS “KEJAM” : PELUANG DAN TANTANGAN - Restiana, Riska (Universitas Nusantara PGRI Kediri, 2016)
Business culinary is a prospective business and never die because everyone definitely need food as long as they still alive. These conditions cause innovations of processed foods that more and more. One of them is innovation of oyster mushroom. Oyster mushroom have a good taste and delicious and also rich nutrition that give many health benefits, other benefits of oyster mushroom are easy to get and the price is classified cheap. In this case the research object is business